Genome-Wide Allele-Specific Expression in Obligately Asexual Daphnia pulex and the Implications for the Genetic Basis of Asexuality. (2nd November 2021) - Ye, Zhiqiang; Jiang, Xiaoqian; Pfrender, Michael E; Lynch, Michael
Abstract: Although obligately asexual lineages are thought to experience selective disadvantages associated with reduced efficiency of fixing beneficial mutations and purging deleterious mutations, such lineages are phylogenetically and geographically widespread. However, despite several genome-wide association studies, little is known about the genetic elements underlying the origin of obligate asexuality and how they spread. Because many obligately asexual lineages have hybrid origins, it has been suggested that asexuality is caused by the unbalanced expression of alleles from the hybridizing species. Here, we investigate this idea by identifying genes with allele-specific expression (ASE) in a Daphnia pulex population, in which obligate parthenogens (OP) and cyclical parthenogens (CP) coexist, with the OP clones having been originally derived from hybridization between CP D. pulex and its sister species, Daphnia pulicaria . OP D. pulex have significantly more ASE genes (ASEGs) than do CP D. pulex . Whole-genomic comparison of OP and CP clones revealed ∼15, 000 OP-specific markers and 42 consistent ASEGs enriched in marker-defined regions. Ten of the 42 ASEGs have alleles coding for different protein sequences, suggesting functional differences between the products of the two parental alleles. At least three of these ten genes appear to be directly involved in meiosis-related processes, for example, RanBP2 can cause abnormal chromosome segregation in anaphase I, and the presence of Wee1 in immature oocytes leads to failure to enter meiosis II. These results provide a guide for future molecular resolution of the genetic basis of the transition to ameiotic parthenogenesis.